Behaviour of a dovetail joint solved using force analyses - Sobra, K (2015)
Dovetail joints are one of the most cornrnonly used joints during Gothic and Baroque periods. Despite being coristructed in the sarne way during the ages, there is no analyticai solution available to help its analysis and design so required in reconstruction works of existing timber structures. An analytical solution based on the principie of virtual works under different types of loading is presented in this paper as weli as differences in bearing capacity of the joint for chosen types of loading, when different wood species are used. The accuracy of the presented solution is confirrned by data obtained from experimental tests of scaied modeis of a dovetail joint.